INDUCED GYNOGENESIS OF COMMON CARP (Cyprinus carpio) AND GRASSCARP (Ctenopharyngodon idella) BY UV-LAMP IRRADIATION - Andrea Kolak (Croatian Journal of Fisheries, 1996)
In this paper the short review of fish gynogenesis, as one of the importani fields of research in ichtiogenetics, is presented. Two methods of own research are described. One of them is mitotic gynogenesis of common carp by 1,1 τ0 Another one is meiotic gynogenesis of grasscarp by 0,2-0,3 τ0. The scientific importance of gynogenetic researches is stated, but also the value of classical genetic methods, which are still more important in practical work.